Description of Amphimonhystrella sinica sp. nov. and Cobbia zhangi sp. nov. of the family Xyalidae (Nematoda: Monhysterida) from the Yellow Sea, China - Huang, Mian; Sui, Xinxin (Zootaxa, 2024)
Two new species of free-living marine nematodes belonging to the family Xyalidae are described from the Yellow Sea, China. Amphimonhystrella sinica sp. nov. is characterized by rhomboid-shaped buccal cavity, circular amphidial fovea relatively far from anterior end of body, slender L-shaped spicules with cephalated proximal end and hooked distal end, tubular gubernaculum with ventrally curved apophyses, slender tail conico-cylindrical with half cylindrical distal part. Cobbia zhangi sp. nov. is characterized by having three similar equal-sized teeth, anterior sensilla arrangement 6+10, slightly curved spicules cephalated proximally and tapered distally, gubernaculum rod-like without apophysis, tail with posterior three fourths filiform part. Updated dichotomous keys to species of Amphimonhystrella and Cobbia are given. Considering the descriptions in the present work, the two genera contain now 9 and 12 valid species, respectively; this study complemented the species diversity of nematodes in Chinese sea area.